Internet Behind Bars: Reality or Utopia? - Fernández-Díaz, Carmen Rocío (IGI Global, 2019)
This chapter focuses on the relevance of information and communication technologies (hereinafter, ICTs) as an essential part of the day-to-day life of all societies nowadays. Nevertheless, a means that continue to be behind this reality is the penitentiary area regarding inmates' rights. Introducing ICTs within prison could improve the social reinsertion of persons serving a prison sentence. Deprivation of liberty entails normal contact with the prison subculture and the harmful effects of it, causing in cases of long-term sentences the so-called phenomenon of “prisonization.” This negative effect of imprisonment could be reduced if ICTs were used inside prisons in the different areas where they can have an impact, and which are treated in this research, as (1) access to information and culture, (2) basic and advanced training, (3) employment, (4) communication with the outside world, (5) treatment, or (6) leisure and entertainment. The value that new technologies would add to these areas in prison constitutes a way of humanization of prisons in the twenty-first century.
La editorial impide el envío del trabajo de investigación completo, por ser su contenido accesible mediante suscripción exclusivamente. Por ello, envío adjunta la muestra gratis que aparece en la web de la revista (https://www.igi-global.com/chapter/internet-behind-bars/210887).
Keywords: Presos; Prisonization; Inmate; Resocialization; Internet; Recidivism; Prison; Information and Communication Technologies